A new device concept for bacterial sensing by Raman spectroscopy and voltage-gated monolayer graphene. Issue 17 (16th April 2019) - Nanda, Sitansu Sekhar; Kim, Bum Jun; Kim, Kwan-Woo; Nasir, Tuqeer; Park, Jaehyun; Yun, Kyusik; Hembram, K. P. S. S.; Papaefthymiou, Georgia C.; Choi, Jae-Young; Yi, Dong Kee
Abstract : Top-gated-monolayer graphene, in the presence of interaction with Gram-positive/negative bacteria, is probed by Raman spectroscopy under an applied voltage. Abstract : Electron–phonon coupling in monolayer graphene results in a modification of its Raman spectra upon charge transfer processes induced by interaction with its chemical environment or the presence of strain or defects in its structure. Modification of Raman spectra is examined in order to develop ultra-sensitive biosensing techniques for the detection, identification, differentiation and classification of bacteria associated with infectious diseases. Specifically, the electrochemical properties of top gated monolayer graphene on SiO2 /Si substrates, in the absence and presence of interaction with Gram-positive bacteria ( Enterococcus faecalis, Bacillus subtilis ) and Gram-negative bacteria ( Escherichia coli and Salmonella typhimurium ), are probed by Raman spectroscopy in an applied voltage range from 0 V to 3 V. Bacteria and monolayer graphene interactions are thus electrostatically tuned. The resulting correlation of specific bacterial chemical properties and Raman spectral characteristics is reported, along with density functional theory simulations of the charge transfer mechanism. The intensities of the G and D Raman vibrational modes are modulated as a function of the applied voltage in the presence of bacteria, but remain unchanged in bare monolayer graphene. A fingerprint region is also identified in the range of 200 cm −1 to 600 cm −1, with disulfide bonds observed at 490 cm −1, associated with bacterial membrane proteins. Significantly, such observations are detected even in the absence of bacterial culturing, a time-consuming step.